SINGLE HYBRIDS OF OKRA FOR PROTECTED CULTIVATION BY FULL DIALLEL CROSSES AND ESTIMATION OF SOME GENETIC PARAMETERS - & Alwan, Al-Karagholi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Field experiment was conducted during 2015 spring season on Okra(Abelmoschus esculentus L.Moench) grown under protected cultivation in the Research and Studies Department - Horticulture Office at Abu Ghraib, to study combining ability and some genetic parameters. Six pure lines ( S1 , S2, , S3 , S4 , S5 , S6 ) were crosses using full diallel crosses. The crosses , parents and hybrid H-597 compared , using RCBD, with tow replicates . Results showed that the promise hybrid in the yield per plant and pods number and the number of flowers was S1 × S3, followed by hybrids S3 × S6 and S5 × S3. The gene action for number of flowers and number of pods in diallel and reciprocal hybrids and the early flowering and yield per plant in diallel hybrid was non additive .pod weight in the diallel and reciprocal early flowering and yield per plants in the reciprocal hybrid from additive one . The broad sense heritability was high for all the studied traits, while the narrow sense heritability were highest for the early flowering, pods number, weight of pods and yield per plant in reciprocal and low in diallel hybrids . The pure lines S1, S3 , S5 had highest general combining ability, while the crosses S1 × S3 , S3 × S6 and S5 × S3 gave the highest specific combining ability, producing the highest plant yield with 553.25, 536.90 and 536.80 g.plant-1, respectively.